Diagrams for Making a Decision on Appropriate Data Processing Methods in the Areas of Health Care and the Social Sciences - Rasnacs, Oskars; Vitins, Maris (International journal of technology, knowledge and society, 2014)
The authors have found that many health care and social science students, as well as practicing specialists, have trouble in relation to the preparation of bachelor’s theses, master’s theses and other scholarly articles when it comes to the use of appropriate data processing methods. Many things have been done in relation to this in the world – appropriate study courses have been introduced at the university level, textbooks have been written, and algorithms have been proposed for the selection of data processing methods in the form of block schemes and tables. That has not, however, been sufficient to make sure that students or specialists can make independent decisions. The purpose of this study is to develop resources that would support the ability of students or specialists to make and implement independent decisions. The authors have surveyed informatics instructors and health care specialists at Latvia’s universities to discuss the subjects that are to be learned and to formulate names for those subjects. The authors have found that it is necessary to arrange concepts that are used in teaching various classes into a structured system. They have designed tables which speak to various situations in data processing, using appropriate sets of words such as statistical indicators, methods and graphics. Examples of appropriate data have been given so that students and specialists can have a better understanding of each situation at hand. The authors have found that such tables, when accompanied by data examples, help students or specialists to make decisions and to improve their educational achievements. The authors are working on the introduction of ontology and on the construction of UML diagrams. They believe that such diagrams, when taken together with data samples, will make it even easier to make decisions and improve learning results.